Through a Glass Darkly: A Fresh Look at the Stories of the Foundation of Singapore (KEMANUSIAAN The Asian Journal of Humanities, 2013)
The story of the founding of Singapore has typically been presented in a "simplistic" manner. This is perhaps understandable for school textbooks but less easy to fathom for specialist or semi-specialist works. Drawing upon sources that have been utilised in the past and those that have rarely been used, such as "The Sincere Letters", this study highlights the intricacies of the manoeuvrings of Stamford Raffles and the Malay rulers at specific junctures to re-evaluate the role of the major participants, particularly Raffles.